Effect of altitude training on skeletal muscle enzymes and immune response of elite triathletes - Wilber, R. L.; Drake, S. D.; Hesson, J. L.; Nelson, J. A.; Kearney, J. T.; Dallam, G. M. (Medicine & Science in Sports & Exercise, 1998)
The effect of five weeks of moderate altitude (11860 m) training on skeletal muscle enzymes, stress hormones, and the immune response of well-trained triathletes were evaluated. Elite junior triathletes (M = 16; F = 8) were tested 7-10 days before going to altitude, within 1.5 days of arriving at altitude, seven days after arrival, 18 days after arrival, and 1.5 days prior to leaving altitude. Only CPK was below normal at the first testing and cortisol was higher on the last testing than at the other times. It was concluded that training at moderate altitude does not induce significant skeletal muscle disruption or immunoreactivity in elite triathletes. Implication: Muscle enzymes and immune system factors are not affected by training at moderate altitude.